PENYELESAIAN SENGKETA TANAH MILIK ADAT MELALUI MEDIASI (Studi Kasus pada Kantor Pertanahan Kota Solok) - Devirianti Effendi; Yenni Fitria (LPPM Universitas Ekasakti Padang, 2022)
Customary land disputes arise because of a concrete relationship between people (legal entities) and their land. The relationship is in the form of use, utilization, ownership and interest, which can lead to disputes. Disputes can be resolved through peaceful means, one of which is mediation, but with the rule of law regarding mediation, its implementation has not been effective because it is seen from the level of dispute resolution through mediation at the Solok City Land Office and the success rate is still low. This research is descriptive in nature using the approach method as the main approach by collecting the necessary literature in the form of books, internet sites and legislation on mediation, the National Land Agency, and is supported by an empirical juridical approach and supported by an empirical juridical approach. The problems that the author discusses are First, How is the implementation of mediation in handling and resolving cases of customary land disputes at the Land Office of Solok City, Second, what are the obstacles faced in resolving disputes through mediation, Third, what laws are carried out in resolving the dispute